Peri-urban land grabbing? dilemmas of formalising tenure and land acquisitions around the cities of Bamako and Ségou, Mali. Issue 3 (4th May 2018) - Neimark, Benjamin; Toulmin, Camilla; Batterbury, Simon
ABSTRACT: This brief note identifies the consequences of land acquisitions in peri-urban spaces around the cities of Bamako and Ségou, Mali. This contributes to debates surrounding the rapid expansion of African cities faced with rapid rural-urban migration and new arrivals settling in precarious conditions. West Africa has a long history of urbanisation, in some cases accompanied by highly productive and intensified land use. It is, therefore, vitally important to question whether formal property rights within peri-urban spaces are a viable option to secure rights for those most marginal and/or recently disposed of their rural land holdings. What are some alternative formalisation mechanisms, which avoid the hazards associated with formal titling, and address the precarious tenure conditions in peri-urban zones?